2020
DOI: 10.1038/s41586-020-2009-2
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-scale single-crystal hexagonal boron nitride monolayers on Cu (111)

Abstract: Ultrathin two-dimensional (2D) semiconducting layered materials offer a great potential to extend the Moore's Law (1). One key challenge for 2D semiconductors is to avoid the formation of charge scattering and trap sites from adjacent dielectrics. The insulating van der Waals layer, hexagonal boron nitride (hBN), is an excellent interface dielectric to 2D semiconductors, efficiently reducing charge scatterings (2, 3). Recent studies have shown the growth of single-crystal hBN films on molten Au surfaces (4) or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
456
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(470 citation statements)
references
References 23 publications
11
456
2
1
Order By: Relevance
“…Graphene and related two-dimensional (2D) materials are a family of exciting materials, which are as small as one to three atoms in vertical direction, but extremely large in horizontal space [1][2][3][4][5]. These systems have attracted significant attention for nanoelectronics and optoelectronics [6][7][8][9][10], non-von Neumann architecture computing [11,12], hybrid flexible and stretchable electronics [13][14][15], and many other applications. As a consequence of their extremely high market value, 2D materials are very attractive to many industries.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and related two-dimensional (2D) materials are a family of exciting materials, which are as small as one to three atoms in vertical direction, but extremely large in horizontal space [1][2][3][4][5]. These systems have attracted significant attention for nanoelectronics and optoelectronics [6][7][8][9][10], non-von Neumann architecture computing [11,12], hybrid flexible and stretchable electronics [13][14][15], and many other applications. As a consequence of their extremely high market value, 2D materials are very attractive to many industries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–4 ] Furthermore, high‐index Cu surfaces, with special symmetries and surface states, provide a promising platform for the epitaxial growth of 2D materials, such as graphene and hexagonal boron nitride. [ 5–10 ] To obtain high‐index Cu single crystals, mechanical cutting of bulk Cu single crystals, [ 11,12 ] and epitaxial deposition of Cu films on single‐crystal inorganic substrates [ 3,13,14 ] are mainly employed, though these approaches remain hindered by the limited size and index choice.…”
Section: Figurementioning
confidence: 99%
“…Two dimensional (2D) materials are potentially the most promising materials for future device applications but in practice, waferscale single crystals of various 2D materials are needed to realize these applications 1,2,3,4 . Recently, the seamless coalescence of millions of unidirectionally aligned islands of a two-dimensional (2D) material epitaxially grown on a substrate has been successfully used to synthesize wafer-scale single crystals of graphene 5,6,7 , hexagonal boron nitride 8,9 and MoS 2 10 , This strategy is expected to be generalized to grow various 2D single crystals in the near future. Nevertheless, the unique behavior of 2D materials growth, different from that predicted by classical theory of epitaxy, necessitates the development of a general theory for the epitaxial growth of 2D materials 5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22 .…”
Section: Mainmentioning
confidence: 99%
“…When grown on Cu(111) or Cu(110) surfaces, triangular hBN islands aligned along two opposite directions were found 13,14,15,28 while those grown on Cu(100) surface had four different orientations 14 . Recent works have shown that the unidirectional alignment hBN islands can be successfully achieved by using a Cu substrate with tailored step edges, thus enabling epitaxial growth of wafer-scale hBN single crystals 8,9 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation